2014
DOI: 10.2516/ogst/2013190
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Binary Mixtures of Propylene and Propane by Facilitated Transport through Silver Incorporated Poly(Ether-Block-Amide) Membranes

Abstract: and available online hereCet article fait partie du dossier thématique ci-dessous publié dans la revue OGST, Vol. 70, n°2, et téléchargeable ici

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…The results show that the propane permeability suffers a slight increase as the silver loading rises. Although the behavior of the paraffin is unusual, similar behavior has been observed in some previous studies, such as those reported by Kim et al [52] and Surya Murali et al [53]. The non-linear trend observed in Figure 4 is an indication that a selective reaction is taking place within the membrane, which is consistent with the facilitated transport mechanism.…”
Section: Permeation Resultssupporting
confidence: 88%
“…The results show that the propane permeability suffers a slight increase as the silver loading rises. Although the behavior of the paraffin is unusual, similar behavior has been observed in some previous studies, such as those reported by Kim et al [52] and Surya Murali et al [53]. The non-linear trend observed in Figure 4 is an indication that a selective reaction is taking place within the membrane, which is consistent with the facilitated transport mechanism.…”
Section: Permeation Resultssupporting
confidence: 88%
“…The best way for the salt to be in the membrane is in the form of free ion, because the silver is more available to the interaction with the olefin. 90,[94][95][96] 45,51,62,84,92,93 poliurethanes (PU) based on polyether or polyester 21,[97][98][99] and poly(ether-block-amide) (best known under the trademark Pebax ® ) 28,100,101 are used as suitable polymer matrix to maintain the dissolution of the silver salts in solid electrolyte membranes. The lower lattice energy of the salt is also crucial in this point to provide an easier way to dissolve the 14 compound.…”
Section: Electrolyte Membranesmentioning
confidence: 99%
“…The best way for the salt to be in the membrane is in the form of a free ion because silver is more available to the interaction with the olefin. , To reach the desired amount of free ions in the electrolyte membrane, normally, the polymer should have suitable functional groups (e.g., ether, amide, lactam, ester, alcohol, and aromatic or aliphatic double bond) to interact with the Ag + cations (Figure a). Polymers like poly­(2-ethyl-2-oxazoline) (POZ), poly­(ethylene oxide) (PEO), polyvinylpyrrolidone (PVP), polymethacrylates (PMA), poly­(vinyl alcohol) (PVA), poly­(styrene- b -butadiene- b -styrene) (SBS), poly­(ethylene phthalate) (PEP), ,,,,, poliurethanes (PU) based on polyether or polyester, , and poly­(ether- block -amide) (best known under the trademark Pebax) ,, are used as suitable polymer matrixes to maintain the dissolution of the silver salts in solid electrolyte membranes. The lower lattice energy of the salt is also crucial to this point to provide an easier way to dissolve the compound.…”
Section: Facilitated Transport Membranes For Olefin/paraffin Separationmentioning
confidence: 99%
“…This is primarily due to their more stable performance, easy processability, good mechanical strength and, of course, lower costs compared to newer materials. In fact, commercial membranes currently used in the industry, such as Matrimid ® , Pebax ® and polysulfones [18][19][20][21], display a moderate combination of permeability and selectivity, and researchers around the world are constantly proposing and developing new and more efficient membrane systems that allow them to substitute these with their advanced materials. Depending on whether high gas volumes need to be processed or whether a high gas purity is needed, research on new materials may be focused either on the gas permeability or on the permselectivity of membranes.…”
Section: Introductionmentioning
confidence: 99%